2018
DOI: 10.1515/cclm-2017-0902
|View full text |Cite
|
Sign up to set email alerts
|

Short- and medium-term biological variation estimates of red blood cell and reticulocyte parameters in healthy subjects

Abstract: This study allowed for estimating the BV of many RBC and reticulocyte parameters, some of which have not been currently explored. For RBC, hemoglobin, RDW-CV and MCV it seems advisable to use RCV calculated according to monitoring time and/or differentiated by sex. As regards analytical goals, we suggest using the most stringent targets found in the short-term arm of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…A systematic review identified more than 30 papers delivering BV data for CBC components, but only four of these studies were assigned a BIVAC grade A [19][20][21][22] and the majority a C or D grade. In our study, meta-analysis of BIVAC compliant studies (grade A, B and C) has enabled publication of updated, global estimates of CV I and CV G for CBC parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review identified more than 30 papers delivering BV data for CBC components, but only four of these studies were assigned a BIVAC grade A [19][20][21][22] and the majority a C or D grade. In our study, meta-analysis of BIVAC compliant studies (grade A, B and C) has enabled publication of updated, global estimates of CV I and CV G for CBC parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Due to stability issues, blood samples cannot be stored and, consequently, the measurement of all samples from the same person cannot be performed in a single centre in a single analytical run on the same day, which is the usual recommended approach. Generally, to obtain reliable BV data of CBC parameters, the protocol and the checklist developed by EFLM BV-WG [17,18] should be followed, as in two recently published national studies [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…5,31,32 Also, intraindividual biological variation for reticulocytes is higher in soccer players compared to inactive subjects. 33,34 Immature reticulocytes are cells with high RNA content which results from the increased rate of bone marrow red cell production. 14 In athletes, high IRF values can be seen in hemolysis, altitude training, and blood manipulation with erythropoietic stimulants.…”
Section: Discussionmentioning
confidence: 99%
“…35 The biological variation for IRF in our soccer players was slightly higher than observed in the non-athletes study population, repeating the same pattern for reticulocytes and RBC parameters. 34…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of imprecision was performed by comparison with the analytical performance specifications for imprecision (CV APS ) of CBC parameters, as described by Buoro et al 28‐30 …”
Section: Methodsmentioning
confidence: 99%